Transforming the Energy of Vacuum by Using the Oscillator Based on Casimir Effect - A. A. Kurayev; V. V. Matveyenka (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2024)
The article shows the possibility of extracting energy from vacuum using an electric oscillator model based on Casimir’s effect with split mirrors rotating relative to each other. Since, according to existing physical concepts, unilateral extraction of energy from vacuum is impossible, the task goes into experimentally detecting tangential forces in Casimir’s effect during the relative rotation of the mirrors that slows down this rotation.